MENAVIGASI BISNIS UMKM PADA MASA PANDEMI COVID-19 - Rizhaldi, Andy; Mahyuni, Luh Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.07.TAHUN.2021, 2021)
Small and Medium Enterprises (SMEs) are important economic entities in Bali, contributing significantly to local and national funds. Especially in Bali, SMEs are often interchangeably linked with tourism, in which both sectors are greatly impacted by the COVID-19 pandemic. A qualitative study was performed to examine the strategies used by Small and Medium Enterprises (SMEs) in order to manage economic crisis during COVID-19 pandemic. An in-depth structured interview was conducted with selected informants. Each interview sessions were recorded after receiving informed consent from informants, then processed into written transcripts. Written transcripts were systematically analyzed and coded into respective themes afterwards. The result of this qualitative descriptive analysis is a scientific model which describes crisis management practices of SMEs during the COVID-19 pandemic era. There were three main factors which support the survival of SMES during COVID-19 struggles; 1) strategic innovations to adapt to changing economic environment during pandemic, 2) implementation of marketing 4.0, and 3) execution of digital businesses strategy. In conclusion, the result of this study suggests the implementation of business processes through digital meanings and social media. Strategic innovations adapting to changing environment is also necessary to provide high-quality yet affordable products in accordance with consumer trend.